Management of financial stability of banks in market conditions - Wu Lige (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the financial stability of banks. The subject of research is the means of maintaining the financial stability of banks in Ukraine. The purpose of the qualifying master's thesis is to deepen the theoretical and methodological foundations of managing the financial stability of banks and to develop scientific and practical recommendations for ensuring financial stability in the modern economy of Ukraine. Based on the results of the research, theoretical and practical provisions have been formulated, leading to concrete proposals for improving the management of financial stability in the banking sector under market conditions. The obtained results include the development of recommendations for enhancing the management of banks' financial stability in Ukraine's economy. These recommendations aim to strengthen the financial position of banks and are applicable to optimizing their organizational structures, developing and implementing both short-term and long-term strategies, and improving current and strategic management practices.
Управління фінансовою стабільністю банків в ринкових умовах
Scientific adviser: Baranova Valeriia, doctor of economics, professor, department banking business and financial technologies
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; financial stability of the bank; indicators of the bank's stability; bank capitalization; financial stability management